2018
DOI: 10.2147/cmar.s176200
|View full text |Cite
|
Sign up to set email alerts
|

Elevated red blood cell distribution width predicts poor prognosis in patients with oral squamous cell carcinoma

Abstract: IntroductionAlthough red blood cell distribution width (RDW) has been reported to reflect inflammation and nutritional status and to predict prognosis in several different types of cancer, little is known about how RDW might be related to oral squamous cell carcinoma (OSCC). The present study aimed to investigate the prognostic value of preoperative RDW in OSCC patients.Materials and methodsWe included 236 OSCC patients from Jinan Stomatological Hospital (Shandong, People’s Republic of China) in this retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Only five studies have examined the relationship of RDW with cancer in the head and neck region, of which one study was for the thyroid cancer (23), two were for cancers of the oral cavity (24, 25) and two were for laryngeal cancers (14, 26). For thyroid cancer, Aktas et al (23) reported that the level of RDW was significantly higher compared with that in normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Only five studies have examined the relationship of RDW with cancer in the head and neck region, of which one study was for the thyroid cancer (23), two were for cancers of the oral cavity (24, 25) and two were for laryngeal cancers (14, 26). For thyroid cancer, Aktas et al (23) reported that the level of RDW was significantly higher compared with that in normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…All these conditions are crucial prognostic factors for severe morbidity and mortality . In adults, RDW is a frequently used predictor for monitoring malignancies and inflammatory diseases, such as pancreatitis and hepatitis . However, there are limited studies on the use of RDW in neonates for monitoring patients and determining their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 In adults, RDW is a frequently used predictor for monitoring malignancies and inflammatory diseases, such as pancreatitis and hepatitis. [18][19][20] However, there are limited studies on the use of RDW in neonates for monitoring patients and determining their prognosis. It has been reported that the increase in RDW in preterm infants may be associated with patent ductus arteriosus, bronchopulmonary dysplasia, and LOS.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, RDW has been used to monitor many different clinical conditions in adults. Increased RDW has been associated with an increased risk of prognosis and mortality, particularly in cases of acute inflammation, such as coronary syndrome or in chronic inflammatory conditions such as malignancies [7,18] . As a mechanism of the increase in RDW value, it has been indicated that inflammatory cytokines inhibit erythrocyte maturation and induce the release of younger and larger reticulocytes into the circulation and thus alter the distribution of erythrocytes [7,10,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Increased RDW has been associated with an increased risk of prognosis and mortality, particularly in cases of acute inflammation, such as coronary syndrome or in chronic inflammatory conditions such as malignancies [7,18] . As a mechanism of the increase in RDW value, it has been indicated that inflammatory cytokines inhibit erythrocyte maturation and induce the release of younger and larger reticulocytes into the circulation and thus alter the distribution of erythrocytes [7,10,18] . In recent years after trials realized in adult patients and older children, studies evaluating the relationship between RDW and morbidities and mortality in newborns have been performed [6,11,12,19,20] .…”
Section: Discussionmentioning
confidence: 99%